2006
DOI: 10.1002/mrd.20600
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Asian yellow goat (C. hircus) by somatic cell nuclear transfer: Telophase enucleation combined with whole cell intracytoplasmic injection

Abstract: Our and other previous studies have shown that telophase enucleation is an efficient method for preparing recipient cytoplasts in nuclear transfer. Conventional methods of somatic cell nuclear transfer either by electro-fusion or direct nucleus injection have very low efficiency in animal somatic cell cloning. To simplify the manipulation procedure and increase the efficiency of somatic cell nuclear transfer, this study was designed to study in vitro and in vivo development of Asian yellow goat cloned embryos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…However, for reconstruction of sei whale iSCNT embryos, ICI seems to be superior to SUZI as evidenced by the higher fusion rates in embryos reconstructed by ICI. Similarly, Chen et al [27] found both embryo reconstruction methods to be effective with respect to embryo developmental potential in Asian yellow goats (C. hircus), although ICI had higher fusion rates than those of SUZI. This indicates that cell fusion conditions including the cell fusion medium should be optimized to obtain satisfactory fusion rates in sei whale iSCNT embryos reconstructed by SUZI.…”
Section: Discussionmentioning
confidence: 90%
“…However, for reconstruction of sei whale iSCNT embryos, ICI seems to be superior to SUZI as evidenced by the higher fusion rates in embryos reconstructed by ICI. Similarly, Chen et al [27] found both embryo reconstruction methods to be effective with respect to embryo developmental potential in Asian yellow goats (C. hircus), although ICI had higher fusion rates than those of SUZI. This indicates that cell fusion conditions including the cell fusion medium should be optimized to obtain satisfactory fusion rates in sei whale iSCNT embryos reconstructed by SUZI.…”
Section: Discussionmentioning
confidence: 90%
“…Although cloning by SCNT is well established in goats, with birth rates similar to those found in other species, there are no reports of cloned goats born in the tropics of the world, between parallels 30 o N and 30 o S, with all cloned goats born in countries under temperate or subtropical climates (Baguisi et al, 1999;Keefer et al, 2001;Reggio et al, 2001;Ohkoshi et al, 2003;Lan et al, 2006;Chen et al, 2007;Folch et al, 2009;Akshey et al, 2010;Colato et al, 2011;Liu et al, 2011;Nasr-Esfahani et al, 2011;Wells et al, 2011;Meng et al, 2012;Zhou et al, 2013;Yuan et al, 2014;Feng et al, 2015;Hosseini et al, 2015;Zhang et al, 2015;Yang et al, 2016a;Bai et al, 2017). This fact may be associated with the low productive and reproductive indexes of goat herds in tropical countries, such as in the Brazilian Semi-Arid region, where the annual birth rate in goats does not exceed 20% (Guimarães, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, better quality oocytes, usually grades I (GI) and II (GII), are selected for in vitro maturation (Chen et al, 2007;Tang et al, 2011). When analyzing data regarding the quality of immature COCs in this study, less than 20% of selected COCs were rated as GI and GII, with a large portion of the COCs lacking or having little cumulus cells vestment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted from tissue collected from the three NT-derived kids that died during the perinatal period and the recipient goats, and analyzed using five microsatellite markers (Table 1) using methods described elsewhere (Chen et al, 2007). The microsatellite alleles for the NT-derived offspring were compared with those from transfected goat donor cells and contrasted with those from the recipient goats that carried the respective pregnancies.…”
Section: Identification Of Transfected Cloned Goatsmentioning
confidence: 99%